Aplikasi Spektrometri Resonansi Magnet Inti 2-Dimensi Untuk Analisis Tumbuhan Obat Tradisional Indonesia - Partomuan Simanjuntak (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
Caesalpinia major Dandy ex Excell is one of the traditional medicinal plants from Nusa Tenggara Timur Province (Flores island, Ruteng) which the local people called as “Dekar". The root of this plant is used as anthelmintic, anti rheumatic, back-ache and also as tonic. Chemical structure elucidation of isolated compound from C. major caesaldekarin A has been done and it's based on ultraviolet, infrared, nuclear nagnetic resonance and mass spectrometry: To know the correlation between proton and proton, proton and carbon, carbon and carbon, NMR two dimensional (2D) have been also interpreted by the data of 'H-'H COSY, 13C-'H COSY, COLOC, HMBC and INADEQUATE. The stereochemistry of the relative structure of caesaldekarin A is determined by 2D NMR NOESY.